Modified sodium ion battery layer oxygen ferric positive electrode material and preparation method thereof
By performing coating and doping treatment in the precursor synthesis and sintering stage of the positive electrode material of sodium ion battery, the iron ion dissolution and ginger Taylor effect caused by high-iron content are solved, and the circulation performance stability and long-term performance of high capacity and low cost are achieved Lifespan is suitable for cost-sensitive fields such as second rounds.
Patent Information
- Application Number
- CN202411426937.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The high iron content in the positive electrode material of sodium ion battery leads to the dissolution of iron ions and the ginger Taylor effect, affecting cycle life and safety performance, and existing solutions have not effectively solved these problems.
By coating in the precursor synthesis stage and element doping and recoating during the sintering stage, a modified sodium ion battery layer oxygen high-speed iron cathode material with Nax (NiaFebMnc)XdYeZfO2 structure was prepared to reduce the ion dissolution caused by the increase in iron content. and phase transition effects.
The cycling performance stability with high capacity and low cost is achieved. The discharge specific capacity of the first circle reaches 142mAh/g. The capacity retention rate of 94.9% is still available for 50 cycles under the 1C current density, showing excellent long cycle life and stability.
Smart Images

Figure CN119230705A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery preparation, and in particular relates to a modified sodium ion battery layered oxygen high iron positive electrode material and a preparation method thereof. Background Art
[0002] With the increasing attention paid to environmental protection and sustainable development around the world, new energy vehicles and energy storage systems, as key technologies to reduce carbon emissions and promote energy structure transformation, are experiencing unprecedented rapid development. Against this background, battery technology, as a core component of energy storage, especially the widespread application of lithium-ion batteries, has achieved remarkable results, but its limited resources (such as uneven distribution of lithium resources and rising costs) and safety issues have gradually become prominent, prompting the scientific research community and the industry to actively explore new battery systems. Sodium-ion batteries, as a potential alternative to lithium-ion batteries, have become a research hotspot in recent years due to their abundant sodium resource reserves, lower cost advantages and similar electrochemical working mechanisms.
[0003] The performance of sodium-ion batteries depends largely on the performance of their cathode materials. An ideal cathode material should have high specific capacity, long cycle life, good rate performance and structural stability. However, the current research on cathode materials for sodium-ion batteries is still in its early stages and faces many challenges, the most critical of which is how to balance the relationship between cost, capacity and cycle stability.
[0004] Among the many positive electrode materials, layered oxygen materials (such as Na x Ni y Mn z Fe 1-y-z O 2 , where x, y, and z are stoichiometric numbers) has attracted much attention due to its adjustable composition, high specific capacity, and relatively good cycle performance. By adjusting the ratio of nickel, manganese, and iron in the material, precise control of material properties can be achieved. In particular, reducing the nickel content and increasing the content of low-priced metal elements such as iron is regarded as an effective cost-cutting and efficiency-increasing strategy. This strategy not only reduces material costs, but also is expected to increase the energy density of the overall battery due to the high theoretical specific capacity of iron (compared to nickel and manganese).
[0005] However, as the iron content increases, a series of problems also arise. First, positive electrode materials with high iron content are prone to dissolution of iron ions during the charging and discharging process, which not only leads to the loss of active materials, but also may cause contamination of the electrolyte, thereby affecting the cycle life and safety performance of the battery. Secondly, when the iron content exceeds a certain threshold (such as 33%), clustering of Fe atoms begins to appear in the material. During the charging process, when the Fe ions are oxidized to +4 valence, these clusters trigger the Jan-Taylor effect, resulting in the migration and phase change of adjacent Fe ions. This phase change is often irreversible, which destroys the crystal structure of the material, resulting in a significant attenuation of the discharge capacity and deterioration of the cycle performance.
[0006] There are many solutions to the above problems. For example, through surface coating modification technology, a stable oxide or phosphate layer can be used to cover the surface of the positive electrode material to inhibit the dissolution of iron ions and improve the cycle stability of the material. It is also possible to finely control the synthesis conditions to achieve uniform distribution of iron, manganese, and nickel elements in the layered oxide material, reduce the formation of iron clusters, and thus alleviate the adverse effects of the Jan-Taylor effect on material performance.
[0007] However, there is no relevant research on the above two solutions. Summary of the invention
[0008] Based on this, the present invention provides a modified sodium ion battery layered oxygen high iron positive electrode material and a preparation method thereof, which effectively reduces the adverse effects of phase change caused by ion dissolution due to increased iron content through coating in the precursor synthesis stage, element doping and re-coating in the positive electrode material sintering stage. Because the modified material has the advantages of high capacity, low cost and stable cycle performance, it can be applied to the second-wheel market and other fields after making battery cells and modules.
[0009] The present invention provides a modified sodium ion battery layered oxygen high iron positive electrode material, comprising a substrate and a precursor stage, a positive electrode stage, a doping stage, and a second layer coating;
[0010] The matrix material is Na x (Ni a Fe b Mn c )X d Y e Z f O 2 ; 0.85≤x<1, 0≤a<0.33, 0.33≤b<0.5, 0≤c<0.33, 0.01≤d<0.05, e=1-abc, 0.01≤f<0.05, X is an oxide of nickel, iron and manganese, Y is one or more elements such as Al, Y, Mg, Ca, Ce, Cu, Ti, etc., and Z is a core-shell structured sodium-based polymer.
[0011] The method for preparing the modified sodium ion battery layer oxygen high iron positive electrode material provided by the present invention comprises the following steps:
[0012] (1) mixing a nickel source, an iron source and a manganese source according to a first molar ratio of nickel, iron and manganese elements to obtain a layered oxygen salt solution 1, and adding the layered oxygen salt solution 1, an alkali solution and a complexing agent to a bottom liquid in parallel to perform a coprecipitation reaction to obtain a layered oxygen precursor;
[0013] (2) mixing a nickel source, an iron source and a manganese source according to a second molar ratio of nickel, iron and manganese elements to obtain a layered oxygen salt solution 2, mixing the layered oxygen salt solution 2, an alkaline solution, a complexing agent and the layered oxygen precursor in step (1), and coating the layered oxygen precursor to obtain the sodium ion battery layered oxygen high iron positive electrode material precursor;
[0014] (3) uniformly mixing the sodium ion battery layered oxygen high iron positive electrode material precursor with a sodium source and a metal compound and then calcining the mixture to obtain a multi-element doped sodium ion battery layered oxygen high iron positive electrode material;
[0015] (4) introducing an inert gas into the solvent, adding polyvinyl alcohol, sodium benzenesulfonate, styrene, magnesium acrylate and zirconium acetate to fully disperse, adding a multi-element doped sodium ion battery layered oxygen high iron positive electrode material, adding an initiator to initiate a polymerization reaction, and obtaining a core-shell structured sodium-based polymer;
[0016] (5) calcining the core-shell structured sodium-based polymer to obtain the modified sodium ion battery layered oxygen high-iron positive electrode material;
[0017] The molar ratio of the iron element in the first molar ratio is higher than or equal to the molar ratio of the iron element in the second molar ratio.
[0018] Specifically, the nickel source is a compound containing nickel, and at least one of nickel sulfate, nickel acetate and nickel nitrate can be preferably selected.
[0019] The manganese source is a compound containing manganese, and at least one of manganese sulfate, manganese acetate and manganese nitrate can be preferably selected.
[0020] The iron source is an iron-containing compound, and preferably at least one of ferrous sulfate, ferrous oxalate and ferrous nitrate can be selected.
[0021] The concentrations of the layer oxygen salt solution 1 and the layer oxygen salt solution 2 are both 1.0-5.0 mol / L;
[0022] The alkali solution is a sodium hydroxide solution, and the concentration of the alkali solution is 2.0-4.0 mol / L.
[0023] The complexing agent is ammonia water, EDTA or sodium citrate, and the concentration of the complexing agent is 1.0-5.0 mol / L.
[0024] Preferably, in step (1), the first molar ratio of nickel, iron and manganese elements is 0.1-0.33:0.33-0.5:0.2-0.35; more preferably, in the embodiment of the present invention, the first molar ratio of nickel, iron and manganese elements is 20-25:45-50:25-30 as an example;
[0025] In step (2), the second molar ratio of nickel, iron and manganese elements is g:h:i, wherein g+h+i=1, h<1 / 3:
[0026] The mass ratio of the layer oxygen salt solution 1 to the layer oxygen salt solution 2 is 1:0.01-0.05.
[0027] Specifically, in step (1), the coprecipitation temperature is 40-60°C;
[0028] In step (2), the particle size D50 of the sodium ion battery layered oxygen high iron positive electrode material precursor is 3.5-10 μm.
[0029] Specifically, in step (3), the sodium source is sodium carbonate, sodium nitrate or sodium hydroxide.
[0030] The metal compound is one or more of aluminum compounds, copper compounds, calcium compounds, cerium nitrate, titanium compounds, yttrium oxide, and magnesium oxide;
[0031] The aluminum compound is aluminum oxide or aluminum nitrate, the copper compound is copper oxide or copper sulfate, the calcium compound is calcium carbonate or calcium nitrate, and the titanium compound is titanium dioxide or titanium tetrachloride;
[0032] The molar ratio of the sodium ion battery layered oxygen high iron positive electrode material precursor to the sodium source and the metal compound is 1:0.9-1.1:0.01-0.05.
[0033] Preferably, the calcination treatment conditions are: calcination temperature is 830-950° C., and calcination time is 10-20 hours.
[0034] Preferably, in step (4), the mass ratio of the multi-element doped sodium ion battery layered oxygen high iron positive electrode material to polyvinyl alcohol, sodium benzenesulfonate, styrene, magnesium acrylate, zirconium acetate and solvent (water or ethanol may be selected) is 100-120: 0.2-2: 5-9: 15-21: 2-5: 0.2-2: 0.1-2: 1000-1200;
[0035] The initiator is azobisisobutyronitrile;
[0036] The polymerization reaction conditions are: reaction at 60° C. for 6 hours.
[0037] Specifically, the calcination treatment conditions are: calcination temperature is 450-650° C., and calcination time is 5-10 hours.
[0038] The present invention also provides a modified sodium ion battery layered oxygen high iron positive electrode material prepared by the preparation method.
[0039] The present invention also provides a sodium ion battery, comprising a positive electrode, a separator and a negative electrode, wherein the positive electrode comprises the modified sodium ion battery layered oxygen high-iron positive electrode material.
[0040] The modified high-iron layer oxygen positive electrode material prepared by the above measures is prepared by coating a relatively stable conventional system in the precursor, doping a specific proportion of transition metals, halogens, rare elements, etc. during the sintering process, and finally coating the core-shell material to effectively improve the rate and cycle performance. Combined with the low-nickel and high-iron component design of the material itself, it takes into account multiple indicators such as cost capacity and performance, which has great advantages for the application of sodium battery materials in cost-sensitive fields such as the second wheel.
[0041] At a current density of 0.1C (voltage window 2-4V), the first-cycle discharge capacity can reach 142mAh / g. At a current density of 1C, the capacity can reach 130mAh / g. After 50 cycles of charge and discharge, there is still a 94.9% capacity retention rate, showing excellent long cycle life and stability. This experimental method is simple and easy, with low material cost. This method can be expanded to be applied to the synthesis of other energy storage materials, thereby improving battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Ni obtained in Example 2 of the present invention 0.25 Fe 0.50 Mn 0.25 (OH) 2 SEM images of precursor materials;
[0043] Figure 2 This is a SEM image of the positive electrode material obtained in Example 2 of the present invention;
[0044] Figure 3 This is a SEM image of the positive electrode material obtained in Example 3 of the present invention;
[0045] Figure 4 0.1C charge-discharge curve diagram of the positive electrode material obtained in Example 2 of the present invention;
[0046] Figure 5 This is a capacity diagram of the positive electrode material obtained in Example 2 of the present invention after 50 cycles at a current density of 1C. DETAILED DESCRIPTION
[0047] Example 1
[0048] Synthesis of precursor: Add 1L pure water to a 5L reactor, add sodium hydroxide and ammonia solution to adjust the pH to 11, maintain constant temperature at 50℃ and stir at a speed of 500r / min, and add NiSO with a total concentration of 2.0mol / L 4 .6H 2 O、MnSO 4 ·H 2 O and FeSO 4 7H 2 O mixed salt solution (Ni:Fe:Mn=25:50:25), 2.0mol / L ammonia water and 4mol / L NaOH solution were added to the reactor in parallel, and the reaction pH was adjusted to 10 for coprecipitation reaction; after the feeding was completed, the salt was replaced with NiSO with a total concentration of 1.0mol / L 4 .6H 2 O、MnSO 4 ·H 2 O and FeSO 4 7H 2 O mixed salt solution (Ni:Fe:Mn=1:1:1) to react, keeping the temperature and pH constant; the mass ratio of the added amount of the first and second batches of salt is 1:0.05;
[0049] The final precipitate was washed with deionized water and dried at 120 °C to obtain the coated Ni 0.25 Fe 0.5 Mn 0.25 (OH) 2 Precursor powder, particle size D50 = 6 μm.
[0050] Synthesis of positive electrode materials: According to the molar ratio of M:Na:Ca:Cu:Ti=1:0.94:0.03:0.005:0.005, the coated Ni 0.2S Fe 0.5 Mn 0.25 (OH) 2 Precursor powder and Na 2 CO 3 Calcium carbonate, copper oxide and titanium dioxide are fully mixed using a high-speed mixer, and then the mixture is sintered in a kiln at a sintering temperature of 900°C and sintered for 15 hours in an air atmosphere to obtain a sodium-based high-iron positive electrode material uniformly doped with calcium, copper and titanium.
[0051] Nitrogen was introduced into water, polyvinyl alcohol, sodium benzenesulfonate, styrene, magnesium acrylate, zirconium acetate were fully dispersed, a calcined sodium electric layer oxygen positive electrode material was added, azobisisobutyronitrile was added as an initiator, heated and stirred at 70°C for 6 hours, filtered, dried, and ground to obtain a core-shell structure sodium-based polymer. The mass ratio of positive electrode material: polyvinyl alcohol: sodium benzenesulfonate: styrene: magnesium acrylate: zirconium acetate: initiator: water is 110:1.5:5:18:3.5:0.8:0.8:1000.
[0052] The sodium-based polymer was sintered in a kiln at 500°C for 8 hours to obtain the final coated sodium battery positive electrode material.
[0053] Example 2
[0054] Synthesis of precursor: Add 1L pure water to a 5L reactor, add sodium hydroxide and ammonia solution to adjust the pH to 11, maintain constant temperature at 50℃ and stir at a speed of 700r / min, and add NiSO with a total concentration of 2.0mol / L 4 .6H 2 O、MnSO 4 ·H 2 O and FeSO 4 7H 2 O mixed salt solution (Ni:Fe:Mn=25:45:30), 5.0mol / L EDTA and 5.0mol / L NaOH solution were added to the reactor in parallel, and the reaction pH was adjusted to 10 for coprecipitation reaction; after the feeding was completed, the salt was replaced with NiSO with a total concentration of 1.0mol / L 4 .6H 2 O、MnSO 4 ·H 2 O and FeSO 4 7H 2 O mixed salt solution (Ni:Fe:Mn=1:1:1) to react, keeping the temperature and pH constant; the mass ratio of the added amount of the first and second batches of salt is 1:0.01;
[0055] The final precipitate was washed with deionized water and dried at 120 °C to obtain the coated Ni 0.25 Fe 0.45 Mn 0.30 (OH) 2 The precursor powder has a particle size of D50 = 7.2 μm, and its SEM image is as follows Figure 1 As shown, there is a certain coating on the surface of the ball.
[0056] Synthesis of positive electrode materials: According to the molar ratio of M: Na: Ca: Al: Ce = 1: 0.90: 0.02: 0.005: 0.005, the coated Ni 0.25 Fe0.45 Mn 0.30 (OH) 2 Precursor powder and Na 2 CO 3 Calcium carbonate, aluminum oxide, and cerium nitrate are fully mixed using a high-speed mixer, and then the mixture is sintered in a kiln at a sintering temperature of 870°C and sintered for 15 hours in an air atmosphere to obtain a uniformly doped sodium-electric high-iron positive electrode material. The SEM image is shown in Figure 2 Shown is a polycrystalline structure.
[0057] Nitrogen was introduced into water, polyvinyl alcohol, sodium benzenesulfonate, styrene, magnesium acrylate, zirconium acetate were fully dispersed, a sodium layer oxygen cathode material was added, and azobisisobutyronitrile was added as an initiator. The mixture was heated and stirred for 6 hours, filtered, dried, and ground to obtain a core-shell sodium-based polymer. The mass ratio of cathode material: polyvinyl alcohol: sodium benzenesulfonate: styrene: magnesium acrylate: zirconium acetate: initiator: water was 100:1:3:13:3:0.5:0.8:1200.
[0058] The sodium-based polymer was sintered in a kiln at 550°C for 10 hours to obtain the final coated sodium battery positive electrode material.
[0059] Example 3
[0060] Synthesis of precursor: Add 1L pure water to a 5L reactor, add sodium hydroxide and ammonia solution to adjust the pH to 11, maintain constant temperature of 50℃ and stir at a speed of 550r / min, and add NiSO with a total concentration of 2.0mol / L 4 .6H 2 O、MnSO 4 ·H 2 O and FeSO 4 7H 2 O mixed salt solution (Ni:Fe:Mn=20:50:30), 3.0mol / L sodium citrate and 8mol / L NaOH solution were added to the reactor in parallel, and the reaction pH was adjusted to 10 for coprecipitation reaction; after the feeding was completed, the salt was replaced with NiSO with a total concentration of 1.0mol / L 4 .6H 2 O、MnSO 4 ·H 2 O and FeSO 4 7H 2 O mixed salt solution (Ni:Fe:Mn=1:1:1) to react, keeping the temperature and pH constant; the mass ratio of the added amount of the first and second batches of salt is 1:0.03;
[0061] The final precipitate was washed with deionized water and dried at 120 °C to obtain the coated Ni 0.20Fe 0.5 Mn 0.30 (OH) 2 Precursor powder, material particle size D 50 =4.1μm.
[0062] Synthesis of positive electrode materials: According to the molar ratio of M:Na:Ca:Y:B:Ti=1:0.94:0.02:0.01:0.015:0.01, the coated Ni 0.20 Fe 0.5 Mn 0.30 (OH) 2 Precursor powder and Na 2 CO 3 Calcium carbonate, yttrium oxide, boric acid, and titanium dioxide are fully mixed using a high-speed mixer, and then the mixture is sintered in a kiln at a sintering temperature of 980°C and sintered in an air atmosphere for 15 hours to obtain a uniformly doped single-crystal sodium-electric high-iron positive electrode material. The SEM image is as follows Figure 3 Shown is the single crystal morphology.
[0063] Nitrogen was introduced into water, polyvinyl alcohol, sodium benzenesulfonate, styrene, magnesium acrylate, zirconium acetate were fully dispersed, a calcined sodium electric layer oxygen positive electrode material was added, azobisisobutyronitrile was added as an initiator, heated and stirred at 70°C for 6 hours, filtered, dried, and ground to obtain a core-shell structure sodium-based polymer. The mass ratio of positive electrode material: polyvinyl alcohol: sodium benzenesulfonate: styrene: magnesium acrylate: zirconium acetate: initiator: water is 120:2:4.5:15:4:1:0.8:1200.
[0064] The sodium-based polymer was sintered in a kiln at 600°C for 10 hours to obtain the final coated sodium battery positive electrode material.
[0065] Example 4
[0066] Synthesis of precursor: Add 1L pure water to a 5L reactor, add sodium hydroxide and ammonia solution to adjust the pH to 11, maintain constant temperature at 50℃ and stir at a speed of 500r / min, and add NiSO with a total concentration of 2.0mol / L 4 .6H 2 O、MnSO 4 ·H 2 O and FeSO 4 7H 2 O mixed salt solution (Ni:Fe:Mn=25:45:30), 4.0 mol / L ammonia water and 5.0 mol / L NaOH solution were added to the reactor in parallel, and the reaction pH was adjusted to 10 for coprecipitation reaction. After the feeding was completed, the salt was replaced with NiSO with a total concentration of 1.0 mol / L 4 .6H 2O、MnSO 4 ·H 2 O and FeSO 4 7H 2 O mixed salt solution (Ni:Fe:Mn=1:1:1) to react, keeping the temperature and pH constant; the mass ratio of the added amount of the first and second batches of salt is 1:0.05;
[0067] The final precipitate was washed with deionized water and dried at 120 °C to obtain the coated Ni 0.25 Fe 0.45 Mn 0.30 (OH) 2 Precursor powder, particle size D50 = 10 μm.
[0068] Synthesis of positive electrode materials: According to the molar ratio of M: Na: Ca: Cu: Mg = 1: 0.91: 0.02: 0.01: 0.005, the coated Ni 0.25 Fe 0.45 Mn 0.30 (OH) 2 Precursor powder and Na 2 CO 3 Calcium carbonate, copper oxide and magnesium oxide are fully mixed using a high-speed mixer, and then the mixture is sintered in a kiln at a sintering temperature of 850°C and sintered for 15 hours in an air atmosphere to obtain a sodium-electric high-iron positive electrode material uniformly doped with calcium, copper and titanium.
[0069] Nitrogen was introduced into water, polyvinyl alcohol, sodium benzenesulfonate, styrene, magnesium acrylate, zirconium acetate were fully dispersed, a calcined sodium electric layer oxygen positive electrode material was added, azobisisobutyronitrile was added as an initiator, heated and stirred at 70°C for 6 hours, filtered, dried, and ground to obtain a core-shell structure sodium-based polymer. The mass ratio of positive electrode material: polyvinyl alcohol: sodium benzenesulfonate: styrene: magnesium acrylate: zirconium acetate: initiator: water is 100:1:3:13:3:0.5:0.8:1100.
[0070] The sodium-based polymer was sintered in a kiln at 450°C for 10 hours to obtain the final coated sodium battery positive electrode material.
[0071] Example 5
[0072] Synthesis of precursor: Add 1L pure water to a 5L reactor, add sodium hydroxide and ammonia solution to adjust the pH to 11, maintain constant temperature at 50℃ and stir at a speed of 500r / min, and add NiSO with a total concentration of 2.0mol / L 4 .6H 2 O、MnSO 4 ·H 2 O and FeSO 4 7H2 O mixed salt solution (Ni:Fe:Mn=25:45:30), 7 mol / L ammonia water and 5 mol / L NaOH solution were added to the reactor in parallel, and the reaction pH was adjusted to 10 for coprecipitation reaction; after the feeding was completed, the salt was replaced with NiSO with a total concentration of 1.0 mol / L 4 .6H 2 O、MnSO 4 ·H 2 O and FeSO 4 7H 2 O mixed salt solution (Ni:Fe:Mn=1:1:1) to react, keeping the temperature and pH constant; the mass ratio of the added amount of the first and second batches of salt is 1:0.05;
[0073] The final precipitate was washed with deionized water and dried at 120 °C to obtain the coated Ni 0.25 Fe 0.45 Mn 0.30 (OH) 2 Precursor powder, particle size D50 = 5.1 μm.
[0074] Synthesis of positive electrode materials: According to the molar ratio of M: Na: Ca: Cu: Mg = 1: 0.91: 0.02: 0.01: 0.005, the coated Ni 0.25 Fe 0.45 Mn 0.30 (OH) 2 Precursor powder and Na 2 CO 3 Calcium carbonate, copper oxide and magnesium oxide are fully mixed using a high-speed mixer, and then the mixture is sintered in a kiln at a sintering temperature of 850°C and sintered for 15 hours in an air atmosphere to obtain a sodium-electric high-iron positive electrode material uniformly doped with calcium, copper and titanium.
[0075] Nitrogen was introduced into water, polyvinyl alcohol, sodium benzene sulfonate, styrene, magnesium acrylate, zirconium acetate were fully dispersed, a calcined sodium electric layer oxygen positive electrode material was added, azobisisobutyronitrile was added as an initiator, heated and stirred at 70°C for 6 hours, filtered, dried, and ground to obtain a core-shell structure sodium-based polymer. The mass ratio of positive electrode material: polyvinyl alcohol: sodium benzene sulfonate: styrene: magnesium acrylate: zirconium acetate: initiator: water is 100:1:3:13:3:0.5:0.8:1200.
[0076] The sodium-based polymer was sintered in a kiln at 550°C for 10 hours to obtain the final coated sodium battery positive electrode material.
[0077] Comparative Example 1
[0078] Synthesis of precursor: Add 1L pure water to a 5L reactor, add sodium hydroxide and ammonia solution to adjust the pH to 11, maintain constant temperature at 50℃ and stir at a speed of 500r / min, and add NiSO with a total concentration of 2.0mol / L 4 .6H 2 O、MnSO 4 ·H 2 O and FeSO 4 7H 2 O mixed salt solution (Ni:Fe:Mn=25:45:30), 2.0mol / L EDTA and 4mol / L NaOH solution were added to the reactor in parallel, and the reaction pH was adjusted to 10 to perform a coprecipitation reaction; after the feeding was completed, the precipitate was washed with deionized water and dried at 120°C to obtain Ni 0.25 Fe 0.45 Mn 0.30 (OH) 2 Precursor powder.
[0079] Synthesis of positive electrode materials: According to the molar ratio of M: Na: Ca: Cu: Ti = 1: 0.91: 0.02: 0.01: 0.005, the coated Ni 0.25 Fe 0.45 Mn 0.30 (OH) 2 Precursor powder and Na 2 CO 3 Calcium carbonate, copper oxide and magnesium oxide are fully mixed using a high-speed mixer, and then the mixture is sintered in a kiln at a sintering temperature of 850°C and sintered for 15 hours in an air atmosphere to obtain a sodium-electric high-iron positive electrode material uniformly doped with calcium, copper and titanium.
[0080] Comparative Example 2
[0081] Synthesis of precursor: Add 1L pure water to a 5L reactor, add sodium hydroxide and ammonia solution to adjust the pH to 11, maintain constant temperature of 50℃ and stir at a speed of 600r / min, and add NiSO with a total concentration of 2.0mol / L 4 .6H 2 O、MnSO 4 ·H 2 O and FeSO 4 7H 2 O mixed salt solution (Ni:Fe:Mn=25:45:30), 10.0mol / L ammonia water and 5.0mol / L NaOH solution were added to the reactor in parallel, and the reaction pH was adjusted to 10 for coprecipitation reaction; after the feeding was completed, the salt was replaced with NiSO with a total concentration of 1.0mol / L 4 .6H 2 O、MnSO4 ·H 2 O and FeSO 4 7H 2 O mixed salt solution (Ni:Fe:Mn=1:1:1) to react, keeping the temperature and pH constant; the mass ratio of the added amount of the first and second batches of salt is 1:0.05;
[0082] The final precipitate was washed with deionized water and dried at 120 °C to obtain Ni 0.25 Fe 0.45 Mn 0.30 (OH) 2 Precursor powder.
[0083] Synthesis of positive electrode materials: According to the molar ratio of M: Na: Ca: Cu: Ti = 1: 0.90: 0.02: 0.01: 0.005, the coated Ni 0.25 Fe 0.45 Mn 0.30 (OH) 2 Precursor powder and Na 2 CO 3 Calcium carbonate, copper oxide and magnesium oxide are fully mixed using a high-speed mixer, and then the mixture is sintered in a kiln at a sintering temperature of 850°C and sintered for 15 hours in an air atmosphere to obtain a sodium-electric high-iron positive electrode material uniformly doped with calcium, copper and titanium.
[0084] Test Example 1
[0085] Preparation of battery pole pieces: Weigh the active material, conductive agent (SP), and binder (PVDF) in a mass ratio of 90:5:5. First, dissolve the weighed 45 mg of active material in a certain amount of NMP solvent, and stir continuously until the active material is completely dissolved; then add PVDF to the active material solution; after PVDF and active material are mixed, add the conductive agent, and then stir continuously. After the active material, SP and PVDF are mixed, use a coater to evenly apply the slurry to the aluminum foil, transfer the copper foil coated with the slurry to a vacuum drying oven and dry it at 120°C for 12 hours; finally, use a cutting machine to cut the dried electrode sheet into a circular electrode sheet with a diameter of 14 mm, and weigh the cut electrode sheet.
[0086] Assembly of CR2032 button cell: In a glove box under argon atmosphere, stack the positive electrode shell, negative electrode sheet, electrolyte, diaphragm, electrolyte, metal sodium sheet, gasket, shrapnel, and negative electrode shell in this order, and then press them into button cells using a sealing machine. After 12 hours of activation, test them. The electrolyte is 1M NaPF 6 / (PC+5%FEC); the separator is made of Whatman glass fiber, and the battery test voltage window is set to 2-4V.
[0087] The test results are shown in Table 1. The 0.1C charge-discharge curve of the positive electrode material obtained in Example 2 is shown in Table 1. Figure 4 The capacity diagram of the positive electrode material obtained in Example 2 of the present invention after 50 cycles at 1C current density is shown in FIG. Figure 5 shown.
[0088] When the capacity of the present invention is tested by cycling 50 times at a current density of 1C, the battery is first cycled once at current densities of 0.1C, 0.2C and 0.5C, and then cycled 50 times at a current density of 1C.
[0089] Table 1 First cycle discharge specific capacity at 0.1C current density and capacity retention rate of 50 cycles at 1C current density of the examples and comparative examples
[0090]
[0091] From Table 1 and Figure 5 The results show that at a current density of 0.1C (voltage window 2-4V), the first cycle discharge capacity of the battery prepared by the positive electrode material obtained in Example 2 is 142mAh / g. At a current density of 1C, the capacity is 130mAh / g, and after 50 cycles of charge and discharge, there is still a capacity retention rate of 94.9%, showing excellent long cycle life and stability.
Claims
1. A method for preparing a modified sodium ion battery layered oxygen high iron positive electrode material, characterized in that: The following steps are involved: (1) mixing a nickel source, an iron source and a manganese source according to a first molar ratio of nickel, iron and manganese elements to obtain a layered oxygen salt solution 1, and adding the layered oxygen salt solution 1, an alkali solution and a complexing agent to a bottom liquid in parallel to perform a coprecipitation reaction to obtain a layered oxygen precursor; (2) mixing a nickel source, an iron source and a manganese source according to a second molar ratio of nickel, iron and manganese elements to obtain a layered oxygen salt solution 2, mixing the layered oxygen salt solution 2, an alkaline solution, a complexing agent and the layered oxygen precursor in step (1), and coating the layered oxygen precursor to obtain the sodium ion battery layered oxygen high iron positive electrode material precursor; (3) uniformly mixing the sodium ion battery layered oxygen high iron positive electrode material precursor with a sodium source and a metal compound and then calcining the mixture to obtain a multi-element doped sodium ion battery layered oxygen high iron positive electrode material; (4) introducing an inert gas into the solvent, adding polyvinyl alcohol, sodium benzenesulfonate, styrene, magnesium acrylate and zirconium acetate to fully disperse, adding a multi-element doped sodium ion battery layered oxygen high iron positive electrode material, adding an initiator to initiate a polymerization reaction, and obtaining a core-shell structured sodium-based polymer; (5) calcining the core-shell structured sodium-based polymer to obtain the modified sodium ion battery layered oxygen high-iron positive electrode material; The molar ratio of the iron element in the first molar ratio is higher than or equal to the molar ratio of the iron element in the second molar ratio.
2. The method for preparing the modified sodium ion battery layered oxygen high iron positive electrode material according to claim 1, characterized in that: The nickel source is at least one of nickel sulfate, nickel acetate and nickel nitrate, The manganese source is at least one of manganese sulfate, manganese acetate and manganese nitrate, The iron source is at least one of ferrous sulfate, ferrous oxalate and ferrous nitrate, The concentrations of the layer oxygen salt solution 1 and the layer oxygen salt solution 2 are both 1.0-5.0 mol / L; The alkali solution is a sodium hydroxide solution, and the concentration of the alkali solution is 2.0-8.0 mol / L. The complexing agent is ammonia water, EDTA or sodium citrate, and the concentration of the complexing agent is 1.0-10.0 mol / L.
3. The method for preparing the modified sodium ion battery layered oxygen high iron positive electrode material according to claim 2, characterized in that: In step (1), the first molar ratio of nickel, iron and manganese elements is 0.1-0.33:0.33-0.5:0.2-0.35; In step (2), the second molar ratio of nickel, iron and manganese elements is g:h:i, wherein g+h+i=1, h<1 / 3; The mass ratio of the layer oxygen salt solution 1 to the layer oxygen salt solution 1 is 1:0.01-0.
05.
4. The method for preparing the modified sodium ion battery layered oxygen high iron positive electrode material according to claim 1, characterized in that: In step (1), the coprecipitation temperature is 40-60°C; In step (2), the particle size D of the precursor of the sodium ion battery layered oxygen high iron positive electrode material is 50 =3.5-10μm.
5. The method for preparing the modified sodium ion battery layered oxygen high iron positive electrode material according to claim 1, characterized in that: In step (3), the sodium source is sodium carbonate, sodium nitrate or sodium hydroxide, The metal compound is one or more of aluminum compounds, copper compounds, calcium compounds, cerium nitrate, titanium compounds, yttrium oxide, and magnesium oxide; The aluminum compound is aluminum oxide or aluminum nitrate, the copper compound is copper oxide or copper sulfate, the calcium compound is calcium carbonate or calcium nitrate, and the titanium compound is titanium dioxide or titanium tetrachloride; The molar ratio of the sodium ion battery layered oxygen high iron positive electrode material precursor to the sodium source and the metal compound is 1:0.9-1.1:0.01-0.
05.
6. The method for preparing the modified sodium ion battery layered oxygen high iron positive electrode material according to claim 5, characterized in that: The calcination treatment conditions are: calcination temperature is 830-950° C., and calcination time is 10-20 hours.
7. The method for preparing the modified sodium ion battery layered oxygen high iron positive electrode material according to claim 1, characterized in that: In step (4), the mass ratio of the multi-element doped sodium ion battery layered oxygen high iron positive electrode material to polyvinyl alcohol, sodium benzene sulfonate, styrene, magnesium acrylate, zirconium acetate and solvent is 100-120: 0.2-2: 5-9: 15-21: 2-5: 0.2-2: 0.1-2: 1000-1200; The initiator is azobisisobutyronitrile; The polymerization reaction conditions are: reaction at 60° C. for 6 hours.
8. The method for preparing the modified sodium ion battery layered oxygen high iron positive electrode material according to claim 1, characterized in that: The calcination treatment conditions are: calcination temperature is 450-650° C., and calcination time is 5-10 hours.
9. A modified sodium ion battery layered oxygen high iron positive electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. A sodium ion battery comprising a positive electrode, a separator and a negative electrode, characterized in that: The positive electrode comprises the modified sodium ion battery layered oxygen high iron positive electrode material according to claim 9.
Citation Information
Patent Citations
Sodium-ion battery cathode materials, preparation method of sodium-ion battery cathode materials, and sodium-ion batteries
CN104953172A
Lithium ferric manganese phosphate positive electrode material with iron and manganese elements in full-concentration gradient distribution and preparation method of lithium ferric manganese phosphate positive electrode material
CN114725340A
Sodium-ion battery positive electrode material, precursor and preparation method
CN115057482A
Core-shell structure type sodium ion battery positive electrode material and preparation method thereof
CN116344731A
Sodium-ion battery concentration gradient oxide positive electrode material and preparation method and application thereof
CN118145718A